Silver nanoparticles confined in shell-in-shell hollow TiO2 manifesting efficiently photocatalytic activity and stability - Zhao, Shidong; Chen, Juanrong; Liu, Yifei; Jiang, Ying; Jiang, Caiguo; Yin, Zhengliang; Xiao, Yingguan; Cao, Shunsheng (Elsevier, 2019)
The complete degradation of tetracycline still is a challenge for TiO2-based photocatalysts under simulated solar light irradiation. To tackle this challenge, we devise Ag nanoparticles (Ag NPs) confined in shell-in-shell hollow TiO2 photocatalyst (HTAT). This strategy mainly involves the construction of CPS@TiO2 core-shell composites, the form of TiO2 inner shell, AgNPs loading by photo-deposition, the assembly of TiO2 outer shell, and phase transition of anatase TiO2 by calcination at 450℃. All characterizations including TEM, STEM Mapping, BET, and XPS confirm the unique structure of the as-synthesized HTAT photocatalyst. As expected, the complete degradation of tetracycline (TC and TCH) can be realized by using HTAT photocatalyst under simulated solar light irradiation because its TiO2 two shells simultaneously take part in the photodegrading reaction of TC or TCH. The transformation intermediates and degradation pathway were analyzed by LC/MS. Our work effectively overcomes the disadvantages of many previously reported TiO2-based photocatalysts for the incomplete degradation of tetracycline.
Keywords: TiO2-Ag@TiO2; Shell-in-shell hollow TiO2; Tetracycline; Confined effect; Degradation mechanism